2019
DOI: 10.3892/ol.2019.11089
|View full text |Cite
|
Sign up to set email alerts
|

TBX3 knockdown suppresses the proliferation of hypopharyngeal carcinoma FaDu cells by inducing G1/S cell cycle arrest and apoptosis

Abstract: The T-box transcription factor family member TBX3 has been demonstrated to participate in the development of various types of cancer, including head and neck squamous cell carcinoma. However, little is currently known about its role in hypopharyngeal carcinoma. In the present study, the involvement of TBX3 in hypopharyngeal carcinoma was investigated. Immunohistochemical assays revealed that TBX3 levels were increased in hypopharyngeal carcinoma compared with normal tissue samples, accompanied by upregulated N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Moreover, the expression of TBX3 was positively correlated with the level of PVT1, which was further confirmed by the result that knockdown of TBX3 visibly reduced the level of PVT1. Thus, these results indicate that transcription factor TBX3 promoted the transcriptional expression of PVT1.The dysregulation of TBX3 has been displayed in breast cancer [30], gastric cancer [31], hypopharyngeal carcinoma [32], and papillary thyroid carcinoma [16]. The present results also showed that the transcriptional and translational expressions of TBX3 were prominently highly expressed in both ATC tissues and FRO cells.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, the expression of TBX3 was positively correlated with the level of PVT1, which was further confirmed by the result that knockdown of TBX3 visibly reduced the level of PVT1. Thus, these results indicate that transcription factor TBX3 promoted the transcriptional expression of PVT1.The dysregulation of TBX3 has been displayed in breast cancer [30], gastric cancer [31], hypopharyngeal carcinoma [32], and papillary thyroid carcinoma [16]. The present results also showed that the transcriptional and translational expressions of TBX3 were prominently highly expressed in both ATC tissues and FRO cells.…”
Section: Discussionsupporting
confidence: 72%
“…Our present data suggested that overexpression of miR-107 promoted the apoptosis. In line with this result, knockdown of TBX3 enhanced the apoptosis of FaDu cells [ 34 ]. In addition, in vivo , we found that miR-107 overexpression reduced tumor volume and weight, and improved the histopathological changes, probably implying the anti-tumor role of miR-107 in FaDu HSCC.…”
Section: Discussionmentioning
confidence: 65%
“…Herein, the overexpression of miR-107 significantly was found to inhibit FaDu cell migration and invasion, consistent with a previous report [ 10 ]. Moreover, cell adhesion molecule E-cadherin acts as a prognostic factor of HPCC [ 34 ]. Active MMP2 and active MMP9 are biomarkers of invasion in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The above selected four genes have been described as potential oncogenes in hypopharyngeal carcinoma [ 10 ], breast cancer [ 11 ], osteosarcoma [ 12 ], and adrenocortical adenomas [ 13 ]. Bisulfite pyrosequencing was used to verify their promoter methylation profiles.…”
Section: Resultsmentioning
confidence: 99%